Localized surface plasmon enhanced deep UV-emitting of AlGaN based multi-quantum wells by Al nanoparticles on SiO2 dielectric interlayer. (16th March 2018) - He, Ju; Wang, Shuai; Chen, Jingwen; Wu, Feng; Dai, Jiangnan; Long, Hanling; Zhang, Yi; Zhang, Wei; Feng, Zhe Chuan; Zhang, Jun; Du, Shida; Ye, Lei; et al.
Abstract: In this paper, we report a 2.6-fold deep ultraviolet emission enhancement of integrated photoluminescence (PL) intensity in AlGaN-based multi-quantum wells (MQWs) by introducing the coupling of local surface plasmons from Al nanoparticles (NPs) on a SiO2 dielectric interlayer with excitons and photons in MQWs at room temperature. In comparison to bare AlGaN MQWs, a significant 2.3-fold enhancement of the internal quantum efficiency, from 16% to 37%, as well as a 13% enhancement of photon extraction efficiency have been observed in the MQWs decorated with Al NPs on SiO2 dielectric interlayer. Polarization-dependent PL measurement showed that both the transverse electric and transverse magnetic mode were stronger than the original intensity in bare AlGaN MQWs, indicating a strong LSPs coupling process and vigorous scattering ability of the Al/SiO2 composite structure. These results were confirmed by the activation energy of non-radiative recombination from temperature-dependent PL measurement and the theoretical three dimensional finite difference time domain calculations.